Hormonal disturbances due to severe and mild forms of congenital adrenal hyperplasia are already detectable in neonatal life. (17th November 2014) - Faurschou, Signe; Mouritsen, Annette; Johannsen, Trine H.; Hougaard, David M.; Cohen, Arieh; Duno, Morten; Juul, Anders; Main, Katharina M.
Abstract Aim National screening programmes for congenital adrenal hyperplasia now include measuring several adrenal metabolites using highly sensitive liquid chromatography–tandem mass spectrometry. The aim of this study was to compare neonatal hormonal profiles – whole blood concentrations of 17α‐hydroxyprogesterone, androstenedione, and cortisol – with genotypes in 21‐hydroxylase deficiency. Methods The study included 62 patients with congenital adrenal hyperplasia born between 1982 and 2012 and 61 random controls born in 1985 and 2005. Patients were grouped according to mutation‐based predictions of enzyme impairment. Groups Null and A were salt‐wasting (n = 35), Group B was simple virilising (n = 7) and Group C was nonclassic (n = 20). Dried blood spot samples were retrieved from the Danish Neonatal Screening Biobank. Results All patients with molecular verified 21‐hydroxylase deficiency had significantly higher concentrations of 17α‐hydroxyprogesterone (p < 0.001), androstenedione (p < 0.001) and a higher ratio [(17α‐hydroxyprogesterone + androstenedione)/cortisol, p < 0.05] than controls. Androstenedione showed a higher sensitivity (72%) than 17α‐hydroxyprogesterone (12%) to correctly identify Groups B and C. Conclusion There were significant differences in neonatal hormonal profiles between all groups and controls. This confirms that hormonal disturbances are already detectable in both severe and mild forms of congenital adrenal hyperplasia in neonatal life.